2002
DOI: 10.1002/jcc.10153
|View full text |Cite
|
Sign up to set email alerts
|

The intramolecular mechanism for the second proton transfer in triosephosphate isomerase (TIM): A QM/FE approach

Abstract: The intramolecular mechanism we earlier proposed [Alagona, G.; Desmeules, P.; Ghio, C.; Kollman, P. A. J Am Chem Soc 1984, 106, 3623] for the second proton transfer of the reaction catalyzed by triosephosphate isomerase (TIM) is examined ab initio at the HF and MP2/6-31+G** levels in vacuo for two conformers of the enediolate phosphate (ENEP), with the ethereal oxygen of the phosphate group either syn (X), as in the crystal structure, or anti (Y) with respect to the enediolate carbonyl O. The barrier height fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The mechanism has been examined by semiempirical QM/MM methods [115,116]. Later, several DFT-based QM/MM studies were been carried out [14,117,17,118]. With a higher resolution structure of the enzyme, Friesner's group modeled the reaction process and obtained results in good agreement with experimental data [119].…”
Section: Applications Of Ab Initio Qm/mm Methodsmentioning
confidence: 97%
“…The mechanism has been examined by semiempirical QM/MM methods [115,116]. Later, several DFT-based QM/MM studies were been carried out [14,117,17,118]. With a higher resolution structure of the enzyme, Friesner's group modeled the reaction process and obtained results in good agreement with experimental data [119].…”
Section: Applications Of Ab Initio Qm/mm Methodsmentioning
confidence: 97%
“…Several theoretical studies, using semiempirical and DFT-based QM/MM methods to study TIM catalysis, have provided an initial atomic-level picture of the various reaction steps (70,(134)(135)(136)(137)(138). Three different paths, involving the key catalytic residues, Glu165 and His95 have been proposed and discussed by several experimental and theoretical groups.…”
Section: Triosephosphate Isomerasementioning
confidence: 99%
“…The protonation state of His95 has been the subject of an active experimental and theoretical discussion. 13,16 NMR studies demonstrated that the imidazole group is neutral at physiological pH values. 32 In the TIM-DHAP Michaelis crystal structure at near-atomic resolution, 1NEY.pdb, the imino N d forms a hydrogen bond with an amidic NH backbone group, and N 1 is tightly hydrogen bonding the substrate O1 and O2, accounting for the repulsive interaction observed in this and previous studies.…”
Section: Dhap-i1mentioning
confidence: 99%